2002
DOI: 10.1007/bf02976988
|View full text |Cite
|
Sign up to set email alerts
|

Biological significance of essential fatty acids/prostanoids/ lipoxygenase-derived monohydroxy fatty acids in the skin

Abstract: The skin displays a highly active metabolism of polyunsaturated fatty acids (PUFA). Dietary deficiency of linoleic acid (LA), an 18-carbon (n-6) PUFA, results in characteristic scaly skin disorder and excessive epidermal water loss. Although arachidonic acid (AA), a 20-carbon (n-6) PUFA, is metabolized via cyclooxygenase pathway into predominantly prostaglandin E2 (PGE2) and PGF2alpha, the metabolism of AA via the 15-lipoxygenase (15-LOX) pathway, which is very active in skin epidermis and catalyzes the transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 76 publications
2
48
0
2
Order By: Relevance
“…10 | 49 MMP-9 signalling, whilst 15-LOX-2 expression was found associated with increased PPAR γ activity and a subsequent reduction in MMP-9 signalling [72,73,74,75], These findings suggest that there is potential for both 15-LOX-1 and 15-LOX-2 inhibitors and metabolites, respectively, to act in an anti-inflammatory and tumour suppressive manner by decreasing cell proliferation and differentiation and inducing apoptosis [76,77,78]. In general, the 5-LOX pathway leads to proliferative and pro-apoptotic effects in various forms of cancer, with exogenous 5-HETE and cysteinyl leukotrienes having up to a fourfold proliferative effect on four different types of breast cancer cell lines [79].…”
Section: Accepted M Manuscriptmentioning
confidence: 95%
“…10 | 49 MMP-9 signalling, whilst 15-LOX-2 expression was found associated with increased PPAR γ activity and a subsequent reduction in MMP-9 signalling [72,73,74,75], These findings suggest that there is potential for both 15-LOX-1 and 15-LOX-2 inhibitors and metabolites, respectively, to act in an anti-inflammatory and tumour suppressive manner by decreasing cell proliferation and differentiation and inducing apoptosis [76,77,78]. In general, the 5-LOX pathway leads to proliferative and pro-apoptotic effects in various forms of cancer, with exogenous 5-HETE and cysteinyl leukotrienes having up to a fourfold proliferative effect on four different types of breast cancer cell lines [79].…”
Section: Accepted M Manuscriptmentioning
confidence: 95%
“…All mammalian cells except erythrocytes convert AA into bioactive eicosanoids (13) using some or all of the following three enzymatic pathways: 1) the cyclooxygenase pathway that leads to the synthesis of numerous prostaglandins, prostacyclins, and thromboxanes (14,15); 2) the lipoxygenase pathway that results in accumulation of hydroperoxides (HPETEs) and leukotrienes (14,15); 3) the AA monooxygenase pathway that creates EETs and HETEs and consists of P450s possessing epoxygenase, lipoxygenase-like, or /-1 hydroxylase activity (16). The first two enzymatic cascades involve multiple P450s responsible for the synthesis of secondary eicosanoids.…”
mentioning
confidence: 99%
“…Galli et al (1994) have also shown in infants that the aberrant EFA profiles preceded the development of AD. GLA is the precursor to prostaglandin E 1 (PGE 1 ), which is antiinflammatory; and when humans consume a diet high in GLA, its metabolic products PGE 1 and 15-hydroxy-eicosatrienoic acid levels accumulate in skin (Ziboh et al 2002;Ziboh and Chapkin 1987;Ziboh and Miller 1990;Ziboh 1994). Saaf et al (2008) recently demonstrated reduced expression levels of the genes for FAD1 FAD2, supporting the hypothesis that the lower levels of PUFA metabolites in AD are due to impaired synthesis.…”
Section: Importance Of Omega-6 Efa In Atopic Dermatitismentioning
confidence: 99%
“…The liver can biotransform LA to GLA, but its rate of transformation can be reduced (e.g., with aging or in subjects under psychological stress; Fan and Chapkin 1998). Human skin is not able to biosynthesize GLA from its precursor acid LA because of a lack of the delta-6 desaturase (Saaf et al 2008;Ziboh et al 2002) and is therefore especially sensitive to changes in the blood levels of GLA. The delta-5 and delta-6 desaturases are considered the rate-limiting enzymes in the formation of long-chain polyunsaturated fatty acids (PUFAs) (Innis 2003;Nakamura and Nara 2004;Sprecher et al 1995).…”
Section: Importance Of Omega-6 Efa In Atopic Dermatitismentioning
confidence: 99%